2007
DOI: 10.1186/1471-2261-7-10
|View full text |Cite
|
Sign up to set email alerts
|

The incidence of myocardial injury following post-operative Goal Directed Therapy

Abstract: Background: Studies suggest that Goal Directed Therapy (GDT) results in improved outcome following major surgery. However, there is concern that pre-emptive use of inotropic therapy may lead to an increased incidence of myocardial ischaemia and infarction.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
7
0

Year Published

2009
2009
2023
2023

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 13 publications
(8 citation statements)
references
References 18 publications
1
7
0
Order By: Relevance
“…This may relate to harmful effects, in particular myocardial ischaemia, when inotropic therapy is administered in high doses. However, more recent GDHT protocols, using only low-dose inotropic therapy, do not appear to be associated with myocardial ischaemia [50]. The importance of the dose of inotropic agents has also been highlighted by the findings of a recent metaregression analysis of five published clinical trials of perioperative dopexamine infusion.…”
Section: Perioperative Goal-directed Haemodynamic Therapymentioning
confidence: 95%
“…This may relate to harmful effects, in particular myocardial ischaemia, when inotropic therapy is administered in high doses. However, more recent GDHT protocols, using only low-dose inotropic therapy, do not appear to be associated with myocardial ischaemia [50]. The importance of the dose of inotropic agents has also been highlighted by the findings of a recent metaregression analysis of five published clinical trials of perioperative dopexamine infusion.…”
Section: Perioperative Goal-directed Haemodynamic Therapymentioning
confidence: 95%
“…In a meta-analysis (8), the use of inotropes in combination with fluids reduced the mortality (OR 0.47, 95% CI 0.29-0.76), and was superior to those studies with only with fluids. Similarly, Pearse et al (95) showed that the pre-emptive use of inotropes in the postoperative management was not associated with an increase of myocardial injury, and as mentioned above, another recent meta-analysis (11) showed that the therapy with fluids and inotropes in high-risk surgical patients was not associated with an increased risk of cardiac complications.…”
Section: Inotropesmentioning
confidence: 94%
“…Interestingly, in the modern era of advanced cardiologic diagnosis and intervention for acute MI, the cause of in-hospital death has shifted from cardiovascular to noncardiovascular [60]. Indeed, several contemporary studies in the nonvascular, noncardiac surgical population demonstrate a significant disconnect between the high rates of cardiac ischemic morbidity seen in the vascular surgical population and far lower rates in other surgical subspecialties [61]. An important shift in emphasis has recently targeted cardiac insufficiency, the prevalence of which continues to rise.…”
Section: Emergence Of Cardiac Insufficiency Rather Than Cardiac Ischementioning
confidence: 97%